Les notions d'autorisation et de consentement dans le contrat médical - Knoppers, Bartha (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
While the terms « authorization » and « consent » are commonly used in juridical language, their definition end precise meaning are not acknowledged by the Quebec legislator. In fact the two terms are often used interchangeably. Both the legislative history of the first paragraph of article 20 of the Civil Code, an article which provides protective measures for the discerning minor entering into a medical contract, and the reforms suggested by the Civil Code Revision Office, demonstrate this confusion as to the proper juridical terms and as to the role of the parental and judicial sanction. The author maintains that the term « consent » is not applicable to the juridical role of the parent of judge.